Analysis of downdraft low rank coal performance gasification by variations coal to syngas product - Erwin Erwin; Aida Syarif; Muhammad Yerizam (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
Coal resources are inclusive (reserves are part of the resource), of which 48% is located in South Sumatra, with 70% of the deposits being brown or low-quality coal. With the high amount available, the direct use of coal has several shortcomings, one of which is that coal releases gases (CO2, N2O, NOx, SOx and Hg) which cause global warming. Coal gasification is a process for converting solid coal into a gas mixture that has a fuel value. Coal gasification will produce producer gas in the form of synthetic gas (syngas) with the main components consisting of carbon monoxide (CO), hydrogen (H2), and methane gas (CH4). By converting coal using gasification as a clean energy producer, a blower as a regulator of air flow, a cyclone as a tar separator and a gas cooler. Based on the results of testing the variation of coal used, the variation of 5515 Kcal / Kg coal has a rapid rise in temperature and is able to produce a flame for 115 minutes. with the composition of Syngas CO and CH4 of 12.4% an 1.2%, while the coal variation of 4640 kcal/kg produces the highest H2 of 6.9%. Coal 5515 kcal/kg produces the largest percentage of syngas conversion, carbon conversion, Low Heating Value, power output and stove efficiency, namely 13.46%, 70.397%, 2.427 MJ/kg, 18.403 KW and 31.23%